The Performance Of Retailing Mix And Customer Relationship Management For Increasing Customer Value And Corporate Image Of PT. Hanan Boga Rasa Cathering, Snack And Bakery - et. al., Mariana Rachmawati , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Along with the times, developments in the retail business are very important for the community, this is due not only to changes in people's shopping patterns which are increasingly selective, but also because of differences in consumer perspectives on the retail business, especially the Cathering Business which was initially seen as merely a provider. food and service alone, is now an increasingly innovative and dynamic business. Research design, this research also carried out through the design, which consists of exploratory, descriptive, and casual categories. Exploratory research is used in this research to clarify the phenomenon and priority of the research problem through analysing expert opinions and views. Descriptive research is used in this research to identify and describe research variables accurately and clearly. This research also creates some hypothesis which are interrelated and described on the research framework that is based on the Structural Equation Modelling system. The analysing unit of this research is the PT Hanan Boga Rasa Chatering Bussines, and the observation unit is the customer. The research result shows that , Most indicators of the Chatering Bussines PT Hanan Boga Rasa retailing mix shows the positive performance, but some of them not showing the good performance , Most indicators of the Chatering Bussines PT Hanan Boga Rasa ’ customer relationship management shows the positive performance, where some of them not showing good performance, i.e.: reward system, customer gathering , The customer value indacators shows the positive performance, especially on the benefit and cost (monetery, time, energy, physic , The image of the gas stations shows the positive performance, except on the personnel and location that need some improvements., The correlation between retailing mix performance and customer relationship management is significant. Eventhough it has a small significant score, this variable should be paid attention, The influence of retailing mix program and the customer relationship management towards the customer value is significant, The influence of retailing mix program and the customer relationship management towards the corporate image is significant . The corellation between customer value and image of the Chatering Bussines PT Hanan Boga Rasa significant.